Making materiality determinations: A context-based approach - Mark W. McElroy (United Nations Research Institute for Social Development (UNRISD), 2019)
Arguably the most important step in the measurement and reporting of an organization's performance is completion of a materiality determination beforehand. At base, materiality determinations address the all-important question of what the scope and criteria for analysis must be in each case, recognizing that in principle no two organizations are alike. Materiality determinations therefore address the question of what the organization specific standards of performance should be - whether social, economic or environmental - and what the corresponding metrics or indicators, too, should be in order to fully assess performance. Even in cases where purportedly universal indicators are being used, the very choice of which ones to in fact use presupposes their relevance. In this paper, we present and advocate for a specific approach for how best to make materiality determinations that are, in the parlance of sustainability management, context-based. As such, the method proposed is normative and triple bottom line in scope, in that it holds organizations accountable for their impacts on all vital capitals and with the well-being of all stakeholders in mind.
Keywords: 330; Context-based sustainability; Impact valuation; Integrated reporting; Materiality; Performance accounting; Rightsholders; Stakeholders; Sustainability accounting; Triplebottom line; Vital capitals